Trajectories of distress from pregnancy to 15-months post-partum during the COVID-19 pandemic - Khoury, Jennifer E.; Jambon, Marc; Giles, Lauren; Atkinson, Leslie; Gonzalez, Andrea (Frontiers in Psychology, 2023)
Background: The COVID-19 pandemic has particularly burdened pregnant and postpartum women. It remains unclear how distress levels of pregnant and postpartum women have changed (or persisted) as the pandemic rages on and which factors may contribute to these trajectories of distress. Methods: This longitudinal study included 304 pregnant women, who were followed during pregnancy, 6-weeks, 6-months and 15-months postpartum. At each time point, a latent “distress” factor was estimated using depression, anxiety, and self-reported stress. Perceived negative impact of COVID-19 and social support were assessed during pregnancy as risk and protective factors related to distress. Second-order latent growth curve modeling with a piecewise growth function was used to estimate initial levels and changes in distress over time. Results: Mean distress was relatively stable from the pregnancy to 6-weeks postpartum and then declined from 6-weeks to 15-months postpartum. Higher education, greater social support, and lower subjective negative impact of COVID-19 were associated with a lower distress during pregnancy. Unexpectedly, greater social support and more negative impact of COVID-19 were associated with a larger increase in distress from pregnancy to 6-weeks postpartum. However, this effect became non-significant after controlling for distress during pregnancy. Conclusions: Findings indicate high but declining levels of distress from pregnancy to the postpartum period. Changes in distress are related to social support and subjective impact of the pandemic in pregnancy. Findings highlight the continued impact of COVID-19 on perinatal mental health and the need for support to limit the burden of this pandemic on pregnant women and families.